Sewing shirts with a perfect fit : The Ultimate Guide to Fit, Style, and Construction from Collared and Cuffed to Blouses and Tunics /: The Ultimate Guide to Fit, Style, and Construction from Collared and Cuffed to Blouses and Tunics. (2018) - Coffin, David Page
No abstract available